PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN,DAN RISIKO PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI - Dwi Ferayani, Made; Devayani Wangsa, Ni Made (Jurnal Daya Saing, 2024)
The purpose of this study is the function of understanding and analyzing the impact of capital structure, company size & company risk on company value in IDX automotive companies. This assessment category is quantitative. Uses secondary data in the form of financial statements & annual reports for the automotive industry published by the Indonesian Stock Exchange for the 2017-2021 period. Data collection techniques with documentation techniques. Using multiple linear regression analysis techniques with SPSS For Windows 25. This study proves that capital structure has a positive and significant influence on company value in automotive companies listed on the IDX, company size has a positive and insignificant effect on the company value of automotive companies listed on the IDX and company risk has a negative & significant effect on the company value in automotive companies listed on the IDX.